Development of protein enriched shrimp crackers from shrimp shell wastes - Khan, M; Nowsad, AKMA (Journal of the Bangladesh Agricultural University, 2013)
A recipe of shrimp cracker (a type of crispy biscuit) enriched with shrimp shell protein was developed from underutilized shrimp shell wastes and the effects of different amount of shrimp shell powders on the quality and shelf life of the products were studied. Shrimp industry wastes (head, appendages, carapaces, and shell) were thoroughly washed, dried in hot air oven at 60°C for 24 h and ground by a blender. Fine shrimp shell powder thus obtained was used for making shrimp crackers. Hydrolyzed vegetable oil, was beaten by hand and other ingredients such as powder milk, sugar, oil, baking powder, flour and vanilla essence were mixed to make a dough. Various levels of shrimp shell powder (5%, 10%, and 20%) were mixed to the dough to enrich with shrimp protein. The dough was kept flatted in a tray, cut into pieces of different shape by dies and put into the oven at 100°C for 8 minutes. Increasing the quantity of shrimp shell powder in shrimp crackers increased the protein content but the quality in terms of taste, color and flavor was slightly decreased. Using of 10% shrimp shell powder obtained the best quality shrimp crackers, in terms of both protein enrichment and sensory quality. Quality of shrimp crackers was tested by both subjective and objective methods. Products made with 10% shrimp shell powder had an acceptable bacterial load in refrigeration up to 45 days but in room temperature up to 30 days. Low storage quality in room temperature might be due to inadequate packaging in the laboratory condition. This research revealed that high quality protein fortified shrimp crackers could be manufactured from unutilized shrimp shell wastes. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14930 J. Bangladesh Agril. Univ. 10(2): 367-374, 2012